Migrant children in Portuguese schools: the case of Brazilian pupils - Seabra, T.; Mateus, S. (Children's lives in Southern Europe: Contemporary challenges and risks, 2020)
European societies are increasingly diverse: in 2015, 76.1 million international migrants were living within Europe (UNICEF, 2016). Of these, about 7 per cent, 5.4 million, are children, presenting different integration challenges for different European countries. This chapter focuses on Portuguese integration policies targeted at children of immigrants, before and during the economic crisis – namely, access to education and vocational training and other opportunities. Our purpose is to discuss children of immigrants’ experiences in Portuguese schools, in particular their family conditions, school paths and future orientations. The discussion is based on national and European reports, previous research, and also draws on data from quantitative research involving children with a Brazilian background. The aim is to acknowledge the experiences and the school paths of the children of Brazilian origin who attend Portuguese basic (elementary) education, and to assess specific challenges, representations and discriminatory practices relating to this group.